Catastrophic flood or inoffensive drizzle: Assessing the impact of countries using the existing water in export subsidies - Laborde Debucquet, David; Díaz-Bonilla, Eugenio (International Food Policy Research Institute, 2015)
This paper has traced the discussions about export subsidies in trade negotiations and highlighted the particular anomaly that while export subsidies in industrial products have been banned under WTO rules, at the time of this writing, they are still allowed for agricultural products, including some that are rather industrialized, such as dairy and meat products. We also noted that, in recent years, the use of export subsidies has been declining (but did not disappear) due to the fact that agricultural and food prices have increased significantly since the lows of the early 2000s. Therefore, those export subsidies were not needed to sell in world markets and the WTO allowances have been above the levels actually utilized (what sometimes is called “water” in the commitments).